IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK MELALUI GERAKAN PADURAKSA DALAM UPAYA MEWUJUDKAN PERLINDUNGAN TERHADAP ANAK DI SMP NEGERI 1 MANTUP LAMONGAN - Nur Afif Ayuni; Raden Roro Nanik Setyowati (Kajian Moral dan Kewarganegaraan, 2025)
The background of this research is the importance of creating a safe and comfortable educational environment for students, through Child-Friendly Schools (SRA). The objectives of this research are to describe the implementation of the Child-Friendly School program through the Paduraksa Movement at SMP Negeri 1 Mantup, to analyze the obstacles to the implementation of Child-Friendly Schools at SMP Negeri 1 Mantup, and to evaluate the implementation of Child-Friendly Schools at SMP Negeri 1 Mantup. This research uses a qualitative approach with a case study research design. Data collection techniques are interviews, observations and documentation. The data validity test used is technical triangulation. Data analysis uses Miles Huberman analysis techniques, with research steps including data collection, data reduction, data presentation, and drawing conclusions. The location of the research is at SMP Negeri 1 Mantup. The research informants are the Principal, BK, TPPK, and students of SMP Negeri 1 Mantup. The results of the study indicate that the implementation of the Child-Friendly School program at SMP Negeri 1 Mantup has reached the Advanced stage, in accordance with the criteria for Child-Friendly Schools in the Paduraksa Movement Technical Guidelines. The obstacles faced were the continued existence of psychological violence between students and the lack of courage of students to report. Based on the evaluation results, this program was successfully implemented in accordance with the criteria for successful policy implementation according to Edward III's Implementation Theory